2011
DOI: 10.1002/masy.201151014
|View full text |Cite
|
Sign up to set email alerts
|

Linear High Molar Mass Polyglycidol and its Direct α‐Azido Functionalization

Abstract: Summary: Linear polyglycidols with narrow chain dispersity and controlled high molar masses were prepared in a few hours by monomer-activated anionic polymerization of protected monomers, ethoxyethyl glycidyl ether and tert-butyl glycidyl ether, using a system composed of tetraoctylammonium bromide as initiator and triisobutylaluminum, used in 1.5 to 5-fold excess compared to the initiator, as coinitiator and monomer activator. This synthetic approach was shown to give various polyglycidol-based copolyethers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…At high monomer conversion, a reactivity decrease is observed due to competitive complexation of iBu 3 Al by the polyether chain. 41 Attempts to increase of the number of aluminum equivalents with respect to the benzyl alcohol did not led to significant improvement of the linearity of the kinetics.…”
Section: Polymerization In the Presence Of A Lewis Acidmentioning
confidence: 97%
“…At high monomer conversion, a reactivity decrease is observed due to competitive complexation of iBu 3 Al by the polyether chain. 41 Attempts to increase of the number of aluminum equivalents with respect to the benzyl alcohol did not led to significant improvement of the linearity of the kinetics.…”
Section: Polymerization In the Presence Of A Lewis Acidmentioning
confidence: 97%
“…At the same time hydride initiation is significantly reduced, which results in almost quantitative initiation of the ammonium salt counterion, e.g., halides or azides . Hence, major drawbacks of the nonactivated anionic ROP of glycidyl ethers are thus overcome, which offers access to high molecular weight poly­(glycidyl ether)­s of up to 100 kDa in short reaction times of only a few hours, suppressing both side reactions and nonuniform functional end groups. The monomer-activated ROP mechanism requires an excess of the aluminum compound with respect to the ammonium salt ([ i- Bu 3 Al]/[NOct 4 Br] > 1) in order to yield high monomer conversions at high speed. ,, Moreover, the reactivity ratios of comonomers can be balanced by increasing the activator-to-initiator ratio . Detailed mechanistic investigations on the monomer-activated anionic ROP of glycidyl ethers in general are reported in the literature. ,, …”
Section: Introductionmentioning
confidence: 99%
“…16−18 The monomer-activated ROP mechanism requires an excess of the aluminum compound with respect to the ammonium salt ([i-Bu 3 Al]/[NOct 4 Br] > 1) in order to yield high monomer conversions at high speed. 17,19,20 Moreover, the reactivity ratios of comonomers can be balanced by increasing the activator-to-initiator ratio. 7 Detailed mechanistic investigations on the monomer-activated anionic ROP of glycidyl ethers in general are reported in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mono- and difunctional potassium alkoxides and sec-BuLi/phosphazene base were used later as initiators [25,26,27,28,29,30]. However, detailed studies of the anionic polymerization of 1-ethoxyethylglycidyl ether revealed that in these processes propagation is accompanied by chain transfer, which leads to polymers with decreased molar masses (see Scheme 6 [28]).…”
Section: Synthesis Of Polyglycidol- and Oilyglycidol-containing Comentioning
confidence: 99%
“…Polymers with higher molar masses (up to 85,000 for poly(1-ethoxyethylglycidyl ether) and 53,000 for poly( tert -butyl glycidyl ether)) were obtained by monomer-activated anionic polymerization initiated with tetraoctylammonium bromide or tetrabutylammonium azide initiators and a triisobutylaluminum catalyst [29,31]. Deblocking of hydroxyl groups in the abovementioned polymers gave polyglycidol samples with M n = 74,000 and 30,200, respectively.…”
Section: Synthesis Of Polyglycidol- and Oilyglycidol-containing Comentioning
confidence: 99%